MAKNA PESAN EDUKATIF SEBAGAI LITERASI DIGITAL DALAM IKLAN LAYANAN MASYARAKAT VERSI #WAKTUNYAKITA KERJASAMA NET TV - Salsabila Perdita Putri; Freddy Yusanto (Prodi Ilmu Komunikasi FISIP Universitas Langlangbuana, 2019)
Social problems are currently a concern that has a major impact on the lives of Indonesians. One way to prevent social problems with ILM on television. One of them is ILM version #waktunyakita kerja sama which aired on Net TV. From the message conveyed in the advertisement, it appears that ILM is one of the digital literature because ILM has a message delivered to audiences, one of which is education. Value education is an educational message that guides audiences to not only get caught in educational materials. Researchers analyzed the clasped video into six scenes and analyzed using Roland Barthes's semiotics and divided them into denotations, connotations and myths. The results show that the ILM version of #waktunyakita kerja sama display the value of social, moral and cultural education messages contained in the ad.